Hubungan Penerapan Pemasaran Digital dengan Peningkatan Pendapatan Usaha Mikro - Edy Suranta Karina Sembiring; Udin Bahrudin (Soratekno Publisher, 2025)
The development of information technology has driven significant changes in marketing strategies, including in the micro-business sector. Digital marketing has become a widely used alternative because it is considered capable of expanding market reach and increasing business competitiveness. This study aims to analyze the relationship between the application of digital marketing and increased micro-business income. The research method used is a quantitative approach with a correlational design. Data was collected through questionnaires distributed to microbusinesses that have implemented digital marketing in their business activities. Data analysis techniques were performed using correlation tests and simple regression analysis to determine the strength and direction of the relationship between variables. The results show that the implementation of digital marketing has a positive and significant relationship with increased microbusiness income. The more optimal the use of digital media, such as social media and online platforms, the greater the opportunity for increased income for business actors. These findings indicate that digital marketing plays an important role in supporting the sustainability and growth of micro businesses in the digital era. This study is expected to be a reference for micro business actors and policy makers in formulating strategies for developing technology-based businesses.